Development of Ethnoscience-Based Physics Teaching Materials on the Topic of Motion Dynamics to Enhance Students’ Critical Thinking Skills - Siti Rodiah; Lovy Herayanti; Baiq Azmi Sukroyanti; Syifa'ul Gummah; Habibi Habibi; María Joselevich (International Journal of Ethnoscience and Technology in Education, 2025)
This study developed and tested the effectiveness of ethnoscience-based physics teaching materials on the topic of motion dynamics to enhance students’ critical thinking skills. A Research & Development approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) was employed. In the Analyze phase, surveys and interviews identified that over 70% of students struggled to understand the concepts of force and acceleration and that the existing materials lacked local contextual relevance. The Design phase produced a framework that integrated the theory of motion dynamics with the Cidomo phenomenon, experimental worksheets, reflective questions, and a critical thinking assessment rubric. All components were produced and validated by two experts in physics ethnoscience, yielding an average S-CVI score of 86% (rating “Highly Feasible”) and strong internal reliability (Cronbach’s α = 0.88). During the Implement phase, 95% of students actively conducted field experiments, 80% posed critical questions, and 70% were able to justify their results based on physics theory. Formative and summative evaluations showed that the average pre-test score increased from 17.75 to 78.75 in the post-test (p < 0.001; Cohen’s d = 5.50). All students achieved a high n-gain category (average g = 0.84). Qualitative data supported the quantitative findings, revealing themes of “Increased Self-Confidence,” “Deep Critical Reflection,” and “Relevance of Local Context.” These results confirm that integrating local cultural context through ethnoscience-based physics teaching materials significantly facilitates the enhancement of students’ critical thinking skills in motion dynamics.